Geometrical Modelling of Stitch class 504 and Jacquard Warp Knitted Fabric (Journal of Fiber Bioengineering and Informatics, 2018)
This research revolves around the geometrical modelling of stitch class 504 and jacquard warp knitted fabric for the prediction of sewing thread consumption for the stitching of an article and for the prediction of yarn consumption in knitted structures and improvement of warp knitting simulation software i.e HZCAD respectively. The thread is a basic fundamental raw material for garment manufacturing industry. After considering thread's performance and appearance the major attention is to resolve the cost. The objective of this project is to develop a geometrical model for stitch class 504, to predict actual required thread consumption and its actual thread cost and to develop the garment. It was concluded that the derived geometrical formula predicted the thread consumption accurately up to 90.34%. In the same way the same geometrical modelling technique was applied on the jacquard wapr knitted favric for the prediction of the yarn consumption also the models were used to improve the warp knitting simulation software. In the industry these geometrical formula can save time and can be helpful in calculating the costing of thread/yarn. It will expand profit margin and save time.
Keywords: Geometrical Modelling; Jacquard Warp Knitted Fabric; Yarn Consumption Estimation; Formula Of Yarn Consumption; Sewing Thread Consumption; Stitch Class 504